Incidence and management of patients with colorectal cancer and synchronous and metachronous colorectal metastases: a population-based study. Issue 4 (16th June 2020) - Väyrynen, V; Wirta, E-V; Seppälä, T; Sihvo, E; Mecklin, J-P; Vasala, K; Kellokumpu, I
Abstract: Background: This population-based study aimed to examine the incidence, patterns and results of multimodal management of metastatic colorectal cancer. Methods: A retrospective population-based study was conducted on patients with metastatic colorectal cancer in Central Finland in 2000–2015. Clinical and histopathological data were retrieved and descriptive analysis was conducted to determine the pattern of metastatic disease, defined as synchronous, early metachronous (within 12 months of diagnosis of primary disease) and late metachronous (more than 12 months after diagnosis). Subgroups were compared for resection and overall survival (OS) rates. Results: Of 1671 patients, 296 (17·7 per cent) had synchronous metastases, and 255 (19·6 per cent) of 1302 patients with resected stage I–III tumours developed metachronous metastases (94 early and 161 late metastases). Liver, pulmonary and intraperitoneal metastases were the most common sites. The commonest metastatic patterns were a combination of liver and lung metastases. The overall metastasectomy rate for patients with synchronous metastases was 16·2 per cent; in this subgroup, 3- and 5-year OS rates after any resection were 63 and 44 per cent respectively, compared with 7·1 and 3·3 per cent following no resection ( P < 0·001). The resection rate was higher for late than for early metachronous disease (28·0 versus 17 per cent respectively; P = 0·048). Three- and 5-year OS rates after any resection of metachronous metastases were 78 and 62 per cent respectively versus 42·1 and 18·2 per cent with no metastasectomy ( P < 0·001). Similarly, 3- and 5-year OS rates after any metastasectomy for early metachronous metastases were 57 and 50 per cent versus 84 and 66 per cent for late metachronous metastases ( P = 0·293). Conclusion: The proportion of patients with metastatic colorectal cancer was consistent with that in earlier population-based studies, as were resection rates for liver and lung metastases and survival after resection. Differentiation between synchronous, early and late metachronous metastases can improve assessment of resectability and survival. Graphical Abstract: In a study of the incidence and management of metastatic colorectal cancer in a population-based cohort, 17·7 per cent of 1671 patients with colorectal cancer had synchronous metastases, and 19·6 per cent of 1302 patients who had resection of stage I–III tumours developed metachronous metastases. In the whole population, the proportion of patients with any metastasis was 33·0 per cent. Metastasis from colorectal cancer